Out of Pocket Payment by Inpatients of Public Hospitals After Health Sector Evolution Plan A Cross-Sectional Study in Tehran City - Ehsan Zarei; Behrooz Pouragha; Soheila Khodakarim; alireza moosazadeh nasrabadi (Tehran University of Medical Sciences, 2017)
Background: One of the main goals of health sector evolution plan is reducing the amount of out of pocket payment by patients receiving hospital services in public sectors. This study aimed to assess the amount of out of pocket payment by inpatients in public hospitals affiliated to Shahid Beheshti University of Medical Science in Tehran city in 2015.   Materials and Methods: In this cross-sectional study, 405 discharged patients from four public and teaching hospitals were selected using convenient sampling method. Data were collected using a researcher made checklist and investigating the hospital bills. In order to data analysis, descriptive statistics and regression analysis were utilized through SPSS Software version16.   Results:  The amount of out of pocket payment was 10.2 percent included 9.9 percent formal payment, 0.2 percent bought & brought goods and 0.1 percent informal payment. The most portion of the hospital costs was related to medical supplies and pharmaceuticals, surgeries services and hosteling with 32.6, 20.6 and 17.36, respectively. Type of hospital, having surgery, average length of stay, family size and gender had significant effect on the out of pocket payment amount (p ≤ 0.05).   Conclusion: The amount of out of pocket payment by inpatient in public hospitals was in accordance with goal of the health sector evolution plan, which reveals the appropriate government support. It is recommended to tailor and implement enormous plans regarding outpatients and private sector in national level to attain sustained reduction in out of pocket payment.